2007
DOI: 10.2460/javma.231.10.1550
|View full text |Cite
|
Sign up to set email alerts
|

Epirubicin in the adjuvant treatment of splenic hemangiosarcoma in dogs: 59 cases (1997–2004)

Abstract: Epirubicin may be as efficacious as adjuvant doxorubicin-based protocols, but may result in a higher incidence of adverse gastrointestinal effects. Epirubicin should be considered as an alternative to doxorubicin in dogs with preexisting cardiac disease, as clinical epirubicin cardiotoxicity was not diagnosed in treated dogs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
62
5
5

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(77 citation statements)
references
References 23 publications
5
62
5
5
Order By: Relevance
“…8,11,13,14 Chemotherapy in the adjuvant setting has been evaluated in various clinical studies and has shown promise in prolonging life after surgical resection of the primary HSA lesion. [15][16][17][18][19] Most of those studies included dogs with different clinical stages of disease.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8,11,13,14 Chemotherapy in the adjuvant setting has been evaluated in various clinical studies and has shown promise in prolonging life after surgical resection of the primary HSA lesion. [15][16][17][18][19] Most of those studies included dogs with different clinical stages of disease.…”
Section: Introductionmentioning
confidence: 99%
“…17,20,21 The most effective chemotherapy protocols for the treatment of canine HSA are anthracycline-based. Doxorubicin and its analog epirubicin have been used: as single agents in the standard 3 wk protocol; in a dose-intense fashion (2 wk protocol); in combination with cyclophosphamide; or with cyclophosphamide and vincristine.…”
Section: Introductionmentioning
confidence: 99%
“…The average life span upon diagnosis of splenic cAS is less than three months for dogs treated with splenectomy alone (Spangler & Culbertson 1992). Dogs treated with adjunctive chemotherapy (usually doxorubicin-based protocols) average less than six months survival (Kim et al 2007;Sorenmo et al 2004). Owners frequently elect to euthanize the dog at the time of diagnosis or shortly thereafter.…”
Section: Prognosis and Treatmentmentioning
confidence: 99%
“…Doxorubicin can induce dose-dependent cardiotoxicities in dogs; the total cumulative dose should not exceed 180-240 mg/m 2 . A study evaluating the potential use of epirubicin in splenectomized cAS patients reported no cardiac toxicity (Kim et al 2007). However, gastrointestinal side effects occurred in a majority of the patients, and neutropenia was also common.…”
Section: Prognosis and Treatmentmentioning
confidence: 99%
See 1 more Smart Citation